2009
DOI: 10.4049/jimmunol.0900713
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Promotes Th2/Th17 Responses via TLR4 and TLR7/8 by Abrogating the Type I IFN Amplification Loop

Abstract: TLR2 plays an important role in the removal of Gram-positive bacteria; contrastingly, it also appears to have important protective effects against unrestrained inflammation and subsequent organ injury during infection and autoimmunity. We hypothesized that TLR2 tunes the phenotype of dendritic cells (DCs) activated through other TLRs, thereby fulfilling a crucial role in the modulation of the immune response. TLR2 potently inhibited TLR4- and TLR7/8-induced cytokine production by human DCs. The inhibitory effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 52 publications
1
42
0
1
Order By: Relevance
“…TLR agonists might be useful not only to boost immunity against microbes and tumors but also to progress autoimmune diseases. Indeed, recent studies have reported that multiple TLR agonists could serve as adjuvants to induce EAE in C57BL/6 mice [26,27]. In our study, APG treatment significantly ameliorated the progression of EAE and down-regulated production of the inflammatory cytokines, IFN-␥, IL-1␤ and IL-17.…”
Section: Discussionmentioning
confidence: 46%
“…TLR agonists might be useful not only to boost immunity against microbes and tumors but also to progress autoimmune diseases. Indeed, recent studies have reported that multiple TLR agonists could serve as adjuvants to induce EAE in C57BL/6 mice [26,27]. In our study, APG treatment significantly ameliorated the progression of EAE and down-regulated production of the inflammatory cytokines, IFN-␥, IL-1␤ and IL-17.…”
Section: Discussionmentioning
confidence: 46%
“…Others have shown that especially TLR2 triggering of DCs can lead to a Th2-cell priming with or without coinduction of Th17 cells [66,67] although there are also other results for Schistosoma antigens that induce Th2-cell responses without the involvement of TLR2, TLR4, or MyD88 [68]. This indicates that quantitatively low TLR signaling but also TLR-and MyD88-independent DC maturation can lead to Th2-cell polarization.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the molecular mechanisms underlying the HCV core/gC1qR-mediated IL-12 suppression, in this study we sought to determine PD-1 and SOCS-1 expression and their role in regulating IL-12 production in human blood-derived M/M F s stimulated with TLR4 ligand-LPS and TLR7/8 ligand-R848, which are known to synergistically induce IL-12 production (35,36). We found that PD-1 and SOCS-1, two negative immunomodulators upregulated by HCV core protein through its interaction with gC1qR on M/M F s, are linked, such that their cross-talk may coordinately deliver negative signaling to TLR-mediated IL-12 production through the Jak/STAT pathway.…”
mentioning
confidence: 99%